2018
DOI: 10.17576/geo-2018-1404-18
|View full text |Cite
|
Sign up to set email alerts
|

The differences of nature experiences between urban and rural children

Abstract: This study aims to investigate the differences between urban and rural children in experiencing nature through direct experiences and indirect experiences, as well as nonnature experiences. Questionnaires were distributed to 760 children from 20 schools located in urban and rural areas in Kedah and Penang, Malaysia. The data were analysed using mean score, standard deviation and one-way analysis of variance. The results confirmed that direct experiences with nature among children in both urban and rural areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(24 reference statements)
0
7
1
Order By: Relevance
“…Unlike some studies (Larson et al, 2018;Mustapa et al, 2018), children in this study favoured nature-based activities while in NPs. Though this discrepancy may arise from methodological differences, the results lend further support to the argument that Maldivian children are still intuitively connected with nature.…”
Section: Preferencescontrasting
confidence: 86%
See 4 more Smart Citations
“…Unlike some studies (Larson et al, 2018;Mustapa et al, 2018), children in this study favoured nature-based activities while in NPs. Though this discrepancy may arise from methodological differences, the results lend further support to the argument that Maldivian children are still intuitively connected with nature.…”
Section: Preferencescontrasting
confidence: 86%
“…Earlier studies have identified opportunities and orientations as broad determinants of children's nature experiences. The contextual basis for these factors is supported by many past studies (e.g., Almeida et al, 2018;Larson et al, 2018;Mustapa et al, 2018;.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations